Characterizing the Use of Botanical Resources from Pollen Loads from Apis mellifera, and Stingless Bees’ Pot-pollen Palynology: An Approach Using Network Analysis and Generalized Linear Models - Breda, Lendra Schuastz; Melo Nascimento, José Elton de; Toledo, Vagner de Alencar Arnaut de; de Lima, Vanderlei Aparecido; Felsner, Maria Lurdes (Sociobiology, 2024)
Pollen loads gathered by honeybees and pot-pollen stored by stingless bees are functional foods with commercial potential. The botanical origin influences the physicochemical composition of the corbicular pollen, Apis mellifera’s bee bread, and the stingless bees’ pot-pollen processed in their nests. Thus, it is vital to determine the factors affecting the botanical composition of these apicultural products. As no prior research on the subject has been conducted, this study examines seasonality and bee species’ impact on the phytogeographic source of honeybee pollen loads and stingless bees’ pot-pollen through the use of palynological analysis, Network Analysis, and Generalized Linear Models (GLM). Due to seasonal variations and abiotic factors, Melipona quadrifasciata quadrifasciata, Melipona marginata, and Scaptotrigona bipunctata stingless bees produced monofloral pot-pollen from plant species within the Myrtaceae, Euphorbiaceae, and Fabaceae families. In contrast, A. mellifera and Tetragona clavipes bees exhibited a more generalist pollen foraging behavior, resulting in heterofloral pollen loads or pot-pollen in most seasons studied. The GLM results indicate that factors including ‘bee species’ and ‘season’ impacted the volume and varieties of pollen gathered by honeybees and stingless bees. It is vital to acknowledge the production area’s characteristics, such as climatic conditions, bee-friendly plants, flower types and quantity, and the behavioral patterns of the bee species regarding pollen foraging. These results highlight the significance of establishing best practices for producing monofloral and heterofloral pollen loads, or pot-pollen. This information may be utilized for commercial applications of A. mellifera pollen loads and stingless bee pot-pollen.